Knowledge, attitude and perception of Nigerian physiotherapists regarding ethics of professional practice (Bangladesh Journal of Bioethics, 2019)
Background of the study: Physiotherapists in Nigeria renewed their practicing license annually through the regulatory body and are provided with the professional code of ethics which stipulate the appropriate conduct, behaviour to guild and regulate the practice of their profession however, the level of knowledge, attitude and application of the ethical guidelines by Nigerian physiotherapists need to be investigated. Aim of Study: This study assessed the knowledge, attitude and perception of Nigerian physiotherapists in relation to the ethics of their professional practice. Methodology: The cross-sectional study recruited 117 licenced Physiotherapists working in various health institutions in Nigeria. They were recruited for the study during the 2018 annual scientific conference of clinical and academic physiotherapists in Nigeria. Data on demographic, work experience, knowledge, attitude and perception of ethics of professional practise were obtained using a self-administered questionnaire. Data were summarized using a descriptive statistics of percentage and frequency distribution. Results: All the participants 117 (100%) had copies of code of ethics and oath of professional practise. 74.6% of participants had good knowledge of code of professional ethics while 25.39% had poor knowledge. Only 40.8% (48) of the respondents demonstrated good attitudes toward code of professional ethics. Similarly, only 43.4% (51) of the respondents demonstrated good attitude towards oath of professional practise. 57.0 % of the respondents have heard about ethical misconduct among colleagues while only 13.60% have been involved in ethical misconduct with respect to colleagues or patients. Greater proportion of the respondents (78.2%) considered ethics in physiotherapy as very important while 43.4% supported the introduction of physiotherapy ethics as a course to physiotherapy students in year three of their undergraduate training. Conclusion: Majority of Nigerian physiotherapists have good knowledge of professional code of ethics and oath of professional practise, however, their attitudes towards periodic updating their knowledge on code of ethics and professional oath remain poor. Clinical implication and recommendation: Ethical matter are very important to the practise of physiotherapy, however the poor attitudes of physiotherapy toward updating their knowledge on ethical matters calls for the need for the regulatory body and the professional association to organise seminars and workshops on ethics in physiotherapy and introduce pre-renewal test on ethics before annual licence renewal.